How to Auction an Essential Facility When Underhand Integration is Possible - Eduardo Engel; Ronald Fischer; Alexander Galetovic (Yale University, Economic Growth Center, 2002)
Regulating seaports is difficult in general, even more so for the weak regulatory institutions common in developing countries. For this reason some countries have awarded these facilities via Demsetz auctions, to the port operator that bids the lowest cargo-handling fee. A major concern with Demsetz auctions in this context, is that the winning operator may integrate with a shipper and monopolize the shipping market, by worsening the service quality for competing shippers. The standard policy recommendation against service quality discrimination is to ban the seaport from operating in the shipping market. The effectiveness of such prohibitions is suspect, however, because they can be circumvented by an (illegal) underhand agreement between the port operator and the shipper. In this paper we show that a ban on integration increases welfare if it is combined with a (sufficiently high) floor on the cargo-handling fee that operators can bid in the auction. In the absence of such a floor, however, a Demsetz auction is worse than no regulation at all of the bottleneck monopoly. Our results apply beyond the port and shipping markets, to any essential facility that can monopolize a downstream market. The results only require that profits with underhand vertical integration agreements be less than with legal vertical integration.
Keywords: D44; L12; L92; 330; auctions; ex ante vs. ex post rents; Demsetz auctions; hidden action; monopoly regulation; productive efficiency; vertical integration; Natürliches Monopol; Regulierung; Auktion; Kartellrecht; Vertikale Integration; Theorie